Effectiveness of Pineapple (Ananas comosus (L) Merr) Ethanol Extract in Inhibiting Microbes in Biofilm on Acrylic Resin Denture Plates - Susanna Halim; Florenly Florenly; Ivanka Ivanka (Jurnal Penelitian Pendidikan IPA, 2024)
Artificial acrylic resin tooth plates can get stained and accumulate plaque with various harmful microorganisms. Hence, a natural ingredient-based denture cleanser is required to prevent or remove extrinsic stains and plaque on the dental plates of acrylic resin dentures. The research objective is to demonstrate the efficacy of pinelapplel elxtract in relmoving or minimizing plaqulel on artificial telelth and to asselss thel elffelct of ulsing pinelapplel elxtract as a clelaning agelnt on thel qulality of lifel of delntulrel welarelrs. This relselarch is a laboratory elxpelrimelnt with a post telst only control groulp delsign. Thel stuldy samplels welrel pulrel culltulrel isolatels of Staphylococculs aulreluls, Elntelrococculs facialis, and Strelptococculs gordonii. This relselarch had six groulps, namelly pinelapplel elthanol elxtract 5%, 10%, 25%, 50%, positivel and nelgativel controls by calcullating thel samplel sizel ulsing thel Feldelrelr formulla and geltting relplication for elach groulp 4 timels. Data welrel elxamineld ulsing onel-way ANOVA and Posthoc LSD statistical melthods. According to thel relselarch findings, it can bel claimeld that pinelapplel elthanol elxtract is elffelctivel in prelvelnting thel growth of Staphylococculs aulreluls, Elntelrococculs faelcalis, and Strelptococculs gordonii bactelria. Thel relselarch conclulsion is that pinelapplel elthanol elxtract can elliminatel or minimizel plaqulel-caulsing microbels on artificial acrylic relsin tooth platels to elnhancel thel qulality of lifel of delntulrel welarelrs